Роль франшиз у сучасному світі та їхній вплив на культуру і суспільство - Базарна, П. А.; Солодов, В. Д. (ХНУРЕ, 2025)
Franchises have become a powerful tool that shapes cultural trends, influences art and political discussions, with their characters defining new social movements. They not only create entertainment but also adapt to contemporary challenges, offering deep narratives and complex characters that reflect real human conflicts and values.
Keywords: франшиза; роль франшиз